The effect of transplantation of cultured autologous melanocytes on CXCL9, CXCL10 and CXCL11 expressions in vitiligo - Chen Xu; Zixian Lei; Li Wang; Hongjuan Wang; Wen Hu; Halina Hairuola; Xiaojing Kang (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo is an acquired chronic autoimmune skin disorder with an estimated prevalence of 1% worldwide. The CD8+ T-cell-mediated chemokines such as CXCR3, CXCL9 and CXCL10 are the non-specific action immunomodulators that are responsible for the depigmentation and progression in vitiligo. Aim: This study aimed to explore the expression levels of serum CXCL9-11 in vitiligo patients who received the transplantation of cultured autologous melanocytes (TCAMs) before and after the operation and correlate their expressions with clinical stage, subtype and course of the vitiligo disease. Materials and Methods: The expression levels of serum CXCL9-11 were measured in the peripheral blood of 26 progressive vitiligo patients, 24 stable vitiligo, 13 TCAM patients and 30 healthy control (HC) cases using enzyme-linked immunosorbent assay (ELISA). The potential correlations between their expressions and disease features such as stage, type and surgical treatment were evaluated using Student's t-test. Results: The expression levels of serum CXCL9-11 increased by ~1.4, ~1.6 and ~2.3-fold in vitiligo patients compared with HCs (P < 0.01). The expression levels of all chemokines were significantly higher in progressive vitiligo patients than in stable vitiligo (P < 0.01). The increasing expression levels of serum CXCL9, CXCL10 and CXCL11 were significantly related to the different types of vitiligo patients (P < 0.05). Preoperative expression levels of serum CXCL9-11 were significantly higher than the post-operative expression levels (P < 0.01). Conclusion: Our results demonstrate that increasing expression levels of the CXC family play a key role in the immunopathogenesis of vitiligo. The abnormal expression of the CXC family may be considered an effective and therapeutic target for TCAM treatment.